Towards Dual-Tracer SPECT for Prostate Cancer Imaging Using [99mTc]Tc-PSMA-I&S and [111In]In-RM2 - Giammei, Carolina; Balber, Theresa; Felber, Veronika; Dillinger, Thomas; Cardinale, Jens; Brandt, Marie R.; Stingeder, Anna; Mitterhauser, Markus; Egger, Gerda; Mindt, Thomas L. (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: Radiolabeled biomolecules specifically targeting overexpressed structures on tumor cells hold great potential for prostate cancer (PCa) imaging and therapy. Due to heterogeneous target expression, single radiopharmaceuticals may not detect or treat all lesions, while simultaneously applying two or more radiotracers potentially improves staging, stratification, and therapy of cancer patients. This study explores a dual-tracer SPECT approach using [111In]In-RM2 (targeting the gastrin-releasing peptide receptor, GRPR) and [99mTc]Tc-PSMA-I&S (targeting the prostate-specific membrane antigen, PSMA) as a proof of concept. To mimic heterogeneous tumor lesions in the same individual, we aimed to establish a dual xenograft mouse model for preclinical evaluation. Methods: CHO-K1 cells underwent lentiviral transduction for human GRPR or human PSMA overexpression. Six-to-eight-week-old female immunodeficient mice (NOD SCID) were subsequently inoculated with transduced CHO-K1 cells in both flanks, enabling a dual xenograft with similar target density and growth of both xenografts. Respective dual-isotope imaging and γ-counting protocols were established. Target expression was analyzed ex vivo by Western blotting. Results: In vitro studies showed similar target-specific binding and internalization of [111In]In-RM2 and [99mTc]Tc-PSMA-I&S in transduced CHO-K1 cells compared to reference lines PC-3 and LNCaP. However, in vivo imaging showed negligible tumor uptake in xenografts of the transduced cell lines. Ex vivo analysis indicated a loss of the respective biomarkers in the xenografts. Conclusions: Although the technical feasibility of a dual-tracer SPECT imaging approach using 111In and 99mTc has been demonstrated, the potential of [99mTc]Tc-PSMA-I&S and [111In]In-RM2 in a dual-tracer cocktail to improve PCa diagnosis could not be verified. The animal model, and in particular the transduced cell lines developed exclusively for this project, proved to be unsuitable for this purpose. The in/ex vivo experiments indicated that results from an in vitro model may not necessarily be successfully transferred to an in vivo setting. To assess the potential of this dual-tracer concept to improve PCa diagnosis, optimized in vivo models are needed. Nevertheless, our strategies address key challenges in dual-tracer applications, aiming to optimize future SPECT imaging approaches.